Synthesis and Antileishmanial Activities of Novel 3-Substituted Quinolines - Tempone, André Gustavo (American Society for Microbiology, 2005)
The antileishmanial efficacy of four novel quinoline derivatives was determined in vitro against Leishmania chagasi, using extracellular and intracellular parasite models. When tested against L. chagasi-infected macrophages, compound 3b demonstrated 8.3-fold greater activity than did the standard pentavalent antimony. No significant activity was found for compounds 3a, 4a, and 4b. The antilesihmanial effect of compound 3b was independent of host cell activation, as demonstrated by nitric oxide production. Ultrastructural studies of promastigotes treated with compound 3b showed mainly enlarged mitochondria, with matrix swelling and reduction in the number of cristae. Synthetic analogues based on the quinoline ring structure, already an established template for antiparasitic drugs, could provide further useful compounds.